2016
DOI: 10.1007/s40615-015-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Residual Effects of Restless Sleep over Depressive Symptoms on Chronic Medical Conditions: Race by Gender Differences

Abstract: Background Sleep and depression are comorbid problems that contribute to the development of chronic medical conditions (CMC) over time. Although racial and gender differences in the bidirectional associations between sleep, depression, and CMC are known, very limited information exists on heterogeneity of the residual effects of sleep problems over depressive symptoms on CMC across race by gender groups. Aim Using a life-course perspective, the present study compared race by gender groups for residual effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 95 publications
7
31
1
Order By: Relevance
“…An extensive research has shown that education (Assari and Lankarani 2016a;Hummer and Lariscy 2011), employment (Assari 2018c), and income (Assari 2018d) have smaller health effects for Blacks than Whites. Similar patterns are also shown for self-efficacy (Assari 2017a(Assari , 2017bAssari and Lankarani 2017), affect (Assari et al 2016;Assari and Burgard 2015;Assari 2017c), and sleep quality (Assari et al 2017b).…”
Section: Introductionsupporting
confidence: 71%
“…An extensive research has shown that education (Assari and Lankarani 2016a;Hummer and Lariscy 2011), employment (Assari 2018c), and income (Assari 2018d) have smaller health effects for Blacks than Whites. Similar patterns are also shown for self-efficacy (Assari 2017a(Assari , 2017bAssari and Lankarani 2017), affect (Assari et al 2016;Assari and Burgard 2015;Assari 2017c), and sleep quality (Assari et al 2017b).…”
Section: Introductionsupporting
confidence: 71%
“…For example, Whites have shorter life expectancies than Blacks when they have few positive emotions (Assari, Moazen‐Zadeh, Lankarani, & Micol‐Foster, ), poorer anger control (Assari, ), lower self‐efficacy (Assari, ), and lower sense of agency (Assari, ). Also, poor sleep (Assari, Sonnega, Leggett, & Pepin, ) and negative emotions (Assari & Lankarani, ) have larger effects on the incidence of chronic disease for Whites compared to Blacks. These papers collectively suggest that health costs associated with fewer psychological assets are greater for Whites than Blacks.…”
Section: A Paradoxical Effectmentioning
confidence: 99%
“…All these studies suggest that positive and negative affect may differently correlate between Blacks and Whites. These findings may help us better understand why correlates of depression and affect vary for Whites and Blacks [ 51 , 52 , 53 ], and why Blacks, who report higher levels of depressive symptoms (negative affect), do not endorse DSM criteria for the clinical disorder [ 29 , 45 , 54 ].…”
Section: Introductionmentioning
confidence: 99%